A microfluidic approach for flexible and efficient operation of a cross-coupling reactive flow. Issue 78 (26th August 2015) - Perazzo, A.; Tomaiuolo, G.; Sicignano, L.; Toscano, G.; Meadows, R. E.; Nolan, S. P.; Guido, S.
<x xml:space="preserve">Abstract</x> A four-feed continuous flow microreactor is exploited for the synthesis of an aromatic amine via a Buchwald–Hartwig reaction, a key bond-forming reaction in the synthesis of a wide range of naturally-occurring and pharmaceutically active targets.